Rodé's theorem on common fixed points of semigroup of nonexpansive mappings in CAT(0) spaces - Watcharapong Anakkamatee (2018)
We extend Rodé's theorem on common fixed points of semigroups of nonexpansive mappings in Hilbert spaces to the CAT(0) space setting. © 2011 Anakkamatee and Dhompongsa; licensee Springer.